Effectiveness of telenursing in improving self-care and blood pressure control among adults with chronic hypertension: a quasi-experimental study in Türkiye - Dursun Alper Yilmaz; Birhat Yakut (Discover Public Health)
Abstract Background Hypertension remains poorly controlled in Türkiye despite advances in pharmacological treatments. Telenursing may help patients improve self-care and blood pressure control. Methods This quasi-experimental pretest-posttest controlled study enrolled 151 adults with chronic hypertension at Ağrı Training and Research Hospital between March 2024 and March 2025. Participants were allocated to an intervention group (n = 76) receiving eight weeks of structured telenursing sessions or a control group (n = 75) receiving usual care. The intervention targeted medication adherence, nutrition, physical activity, stress management, and self-monitoring. Primary outcomes were blood pressure indices and hypertension self-care profile (HTN-SCP) scores. Results After the intervention, the intervention group exhibited greater reductions in systolic blood pressure (mean Δ = −8.6 mmHg, p = 0.001), pulse pressure (p = 0.001), and mean arterial pressure (p = 0.003) compared to controls. HTN-SCP self-efficacy scores increased significantly (from 52.4 to 56.1, p < 0.001, r = 0.53). While participants adopting a combined approach of medication, diet, and exercise scored higher than those using medication alone (p = 0.015), this finding should be interpreted cautiously due to the very small subgroup size. This study provides novel evidence supporting the feasibility and effectiveness of structured telenursing in enhancing self-care and blood pressure control in resource-limited settings. Conclusion Telenursing is a feasible and effective digital health strategy to improve self-care and blood pressure control, supporting sustainable hypertension management in low-resource contexts.